2021
DOI: 10.3390/brainsci11060676
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 4 Weeks of Chiropractic Spinal Adjustments on Motor Function in People with Stroke: A Randomized Controlled Trial

Abstract: Chiropractic spinal adjustments have been shown to result in short-term increases in muscle strength in chronic stroke patients, however, the effect of longer-term chiropractic spinal adjustments on people with chronic stroke is unknown. This exploratory study assessed whether 4 weeks of chiropractic spinal adjustments, combined with physical therapy (chiro + PT), had a greater impact than sham chiropractic with physical therapy (sham + PT) did on motor function (Fugl Meyer Assessment, FMA) in 63 subacute or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Therefore, investigating whether chiropractic spinal adjustment can increase muscle strength and impact walking function in people with stroke can be important for future research. In line with this importance, recently, Holt et al (40) has found clinically significant improvements in motor function following a combination of chiropractic spinal adjustment and physical therapy. It is also postulated that spinal adjustment might affect neural functionality (12,13) in people with chronic stroke.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, investigating whether chiropractic spinal adjustment can increase muscle strength and impact walking function in people with stroke can be important for future research. In line with this importance, recently, Holt et al (40) has found clinically significant improvements in motor function following a combination of chiropractic spinal adjustment and physical therapy. It is also postulated that spinal adjustment might affect neural functionality (12,13) in people with chronic stroke.…”
Section: Introductionmentioning
confidence: 83%
“…This is a basic science study; therefore, the results from this study should not be extrapolated to clinical implications for the chronic stroke population. For clinical implication, Holt et al (40) has found clinically significant improvements in motor function following a combination of chiropractic spinal adjustment and physical therapy. Further work is required to explore what potential clinical implications chiropractic care may have for different stages of stroke progression, which needs to be further investigated in future studies.…”
Section: Study Considerationsmentioning
confidence: 99%
“…Although the mechanisms are not fully understood, chiropractic manipulative therapy increases the cortical intrinsic inhibitory interactions in patients with chronic pain [16,17], normalizes muscle tone, and inhibits spasms [18]. Other studies have also shown that chiropractic adjustments can increase the dorsiflexor muscle strength and walking gait in stroke patients [19,20]. Pregnant women in their second trimester also experience more relaxation of the pelvic floor muscles after chiropractic treatment [21].…”
Section: Discussionmentioning
confidence: 99%